Registration of 'Surefire' Winter Canola. Issue 3 (1st September 2019) - Stamm, Michael; Angadi, Sangu; Damicone, John; Dooley, Scott; Holman, Johnathon; Johnson, Jerry; Lofton, Josh; Santra, Dipak
Abstract : 'Surefire' (Reg. no. CV‐27, PI 689513) is a winter canola ( Brassica napus L.) cultivar that possesses tolerance to sulfonylurea herbicide carryover in the soil. Surefire will replace 'Sumner', which was the first winter canola cultivar released with this tolerance for the southern Great Plains. Sulfonylurea herbicides, or acetolactate synthase (ALS) inhibitor herbicides, have significant plant‐back restrictions for susceptible crops, and they often limit rotating to canola in wheat ( Triticum aestivum L.)–based cropping systems. Planting tolerant cultivars allows canola producers to avoid the plant‐back restrictions. Surefire was released by K‐State Research and Extension and was tested under the experimental name KSUR1211. Surefire drew attention in the 2012–2013 growing season as an entry in the sulfonylurea residual tolerance yield trial. It was the top‐ranked cultivar at Hutchinson and Manhattan, KS, averaging 3452 and 4232 kg ha −1, respectively. Across Great Plains sites of the 2015–2016 and 2016–2017 National Winter Canola Variety Trial, Surefire averaged 522 kg ha −1 more than Sumner. Surefire is about 4.2 d later to 50% bloom than Sumner. Surefire does not differ from Sumner in its tolerance to sulfonylurea herbicide carryover. The later maturity of Surefire gives it a distinct yield advantage over Sumner as fuller‐season cultivars typically yield more than early‐maturity cultivars.